RESPONS BEBERAPA VARIETAS KEDELAI (Glycine max L.) TERHADAP PEMBERIAN PUPUK GUANO - Sandi Gumilar; Jonis Ginting; Sanggam Silitonga (Jurnal Agroekoteknologi, 2013)
Soybean production is influenced by the variety and nutrients available in the soiland plant roots can absorb. This research means to test the response of severalvarieties of soybean (Glycine max L.Merill) for guano fertilizer. Location of theresearch was conducted in the Tanjung Selamat village, Deli Serdang regency,using a randomized block design of two factors they are varieties (Anjasmoro,Burangrang and Argomulyo ) and guano doses (250, 300, 350, 400 and 450kg/ha). The parameters observed were plant height, branch number produtive,number of pods per sample, the number of filled pods per sample,number ofempty pods per sample, weight of dry seed per sample, weight of dry seed perplot, weight of 100. The results showed that varietie significantly influenced toplant height, branch number produtive, number of pods per sample, the number offilled pods per sample,number of empty pods per sample, weight of dry seed persample, weight of dry seed per plot, weight of 100. Varieties and fertilizertreatment interaction effect was not apparent guano on all parameters.Key word : soybean, variety, guano